REHABILITATION IN NEUROTRAUMAS: APPROACHES AND PROSPECTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Neurotrauma rehabilitation is a complex of measures aimed at restoring lost functions of the central and peripheral nervous systems following traumatic brain and spinal cord injuries. Given the high incidence of disability and long recovery times, neurorehabilitation is becoming a key area of modern medicine, improving patients' quality of life and their social adaptation.